How to think about media policy silence. (March 2021) - Li, Luzhou
Using 'media policy silence' as a construct, this article discusses three types of policy practices that are marked by policy opacity rather than policy visibility, by the absence of formal policy or 'un-decisions' rather than decisions and by policy inertia rather than intervention. They are, respectively, first, the 'elephant in the room' type of silence that mostly refers to lacunae in policy outcomes and agendas; second, policy 'undecisions' (i.e. policy scenarios in which no formal policy decisions take place); and last, 'considered silence' that refers to government non-intervention. I will talk about these three different types of media policy silence and their relationships by drawing upon existing literature, using examples from different political and regulatory contexts, and where appropriate, reflecting on the methodological challenges that those silences pose to traditional policy research. To sum up, the article intends to identify the opposite side of the official and formal policy sphere.